Effect of adding poultry manure and spraying organic acids on yield and some components of potato ( salanum tuberosuml.) - AL-Tememe, Mohammed Sallal; AL-Jadiri, Dhay Mohammed (Journal of Kerbala for Agricultural Sciences, 2018)
A field experiment was carried out in one of farms in Babylon distract Abi Garaq of a 10 am soil texture , to study the effect of organic fertilization application ( poultry wastes) and foliar application of humic and folric acid )and interaction between them on the growth and yield of Potato . This experiment included three levels of organic fertilizer ( poultry wastes ) at 0 , 5 , 10 Ton.ha-1 . First factors named F0 , F1 , F2 respectively , while the second factors of foliar application of organic acids ( humic and folvic acid ) named as S0 , S1 , S2 at 0 , 5 , 10 ml.L-1 respectively at a total of nine treatment in three application of a total experimental units of 27 . They experiment was carried out under RCBD , Potato tubers class Burren were planted on 16 / 1 / 2017 .At maturity , total percentage of proteins and starch of the total yield and tubers number at the end of season were measured. Data was statistically analyzed and means were compared according to least signification different test at 0.05 level of probability . Result show :- Organic fertilization ( poultry wastes ) F2 was supervisor as compared to F1 and F0 in plant total tubers yield 28.70 Mg ha-1 , number of tubers 6.96 tuber plant-1 , total tuber dry weight percentage 28.70%.Organic fertilization of poultry wastes , treatment F2 was superior when compared to F1 and F0 by giving the highest percentage of protein and starch tubers at 10.19% and 11.0 % respectively . Foliar application of organic acid ( humic and folivc ) have shown super iorvity in studied porameters of F2 treatment when compared to S1, S0 treatment where it caused a signification increase in total tubers yield , number of tubers , at highest values of means at 25.29 Mg ha-1 , 7.82 tuber . per 17.73 % of each respectively .Organic acids foliar application treatment S2 was superior to S1 , S0 by giving highest means of protein and starch percentage in tubers at 9.56 , 11.71% respectively . F2S2 interaction treatment has given the highest values of studies parameter where they were 10.31 % , 12.43 % of protein and starch percentage in tubers respectively . 4. 30.73 M gm ha-1 of total yield of tubers , 8.83 tuber plant-1 .